Comparison of the corticosteroid injection and hyaluronate in the treatment of chronic subacromial bursitis: A randomized controlled trial. (September 2021) - Hsieh, Lin-Fen; Lin, Yi-Jia; Hsu, Wei-Chun; Kuo, Ying-Chen; Liu, Yu-Chia; Chiang, Yi-Pin; Wang, Chun-Ping
Objective: To analyse the effectiveness of corticosteroid (CS) and hyaluronic acid (HA) subacromial – subdeltoid (SASD) injection compared with normal saline (NS) in patients with chronic subacromial bursitis (CSB). Design: A prospective three-arm double-blinded randomised controlled trial. Setting: Rehabilitation department of two teaching hospitals. Subjects: Patients with CSB ( N  = 186) divided into CS ( N  = 68), HA ( N  = 60), and NS ( N  = 58) groups. Interventions: Three SASD injections under ultrasound guidance: group A, 20 mg of triamcinolone; group B, 2.5 mL of HA; and group C, 2.5 mL of NS. Outcome measures: The primary outcome measures were the pain visual analogue scale (VAS) score at eight weeks. The secondary outcomes were scores on the Shoulder Pain and Disability Index (SPADI) and Shoulder Disability Questionnaire. Results: At eight weeks, the pain VAS scores during activity were 2.56 ± 2.29, 3.65 ± 2.50, and 4.71 ± 2.83 in the CS, HA, and NS groups, respectively (CS vs NS, P  < 0.001; HA vs NS, P  = 0.013; CS vs HA, P  = 0.010). SPADI scores were 40.83 ± 21.75, 36.92 ± 22.78, and 33.35 ± 23.38 in the CS, HA, and NS groups, respectively (CS vs NS, P  < 0.001; HA vs NS, P  = 0.197; CS vs HA, P  = 0.004). Conclusion: Ultrasound-guided corticosteroid injection into the subacromial – subdeltoid bursa was proven to be effective and superior to hyaluronic acid and normal saline injection for treating CSB. Hyaluronic acid injection was only marginally more effective than normal saline injection. Trial Registration: ClinicalTrials.gov: NCT02702206